2020
DOI: 10.1159/000512196
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin: Plants of the Genus <b><i>Capsicum</i></b> and Positive Effect of Oriental Spice on Skin Health

Abstract: <b><i>Background:</i></b> Capsaicin, the main pungent ingredient in hot chili peppers, causes excitation of small sensory neurons. It also provides the basic pungent flavor in <i>Capsicum</i> fruits. <b><i>Summary:</i></b> Capsaicin plays a vital role as an agonist for the TRPV1 (transient receptor potential cation channel, subfamily V, member 1) receptor. TRPV1 is essential for the reduction of oxidative stress, pain sensations, and inflammation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…Capsaicin (8-methyl-6-nonanoyl vanillylamide) is a nonpolar phenol, which is why washing skin that has come in contact with capsaicin with water or vinegar alone is insufficient to solubilize it. 13 Capsaicin binds to the transient receptor potential vanilloid 1 (TRPV1), a calcium channel on neurons that opens in response to heat. When bound, the channel opens at a lower temperature threshold and depolarizes nerve endings, leading to vasodilation and activation of sensory nerves.…”
Section: Irritant Chemicalsmentioning
confidence: 99%
“…Capsaicin (8-methyl-6-nonanoyl vanillylamide) is a nonpolar phenol, which is why washing skin that has come in contact with capsaicin with water or vinegar alone is insufficient to solubilize it. 13 Capsaicin binds to the transient receptor potential vanilloid 1 (TRPV1), a calcium channel on neurons that opens in response to heat. When bound, the channel opens at a lower temperature threshold and depolarizes nerve endings, leading to vasodilation and activation of sensory nerves.…”
Section: Irritant Chemicalsmentioning
confidence: 99%
“…Reduction in the production of osteoblasts or increase in the incidence of osteoclasts is considered to be the main cause of osteoporosis. [57] Olive oil can also be beneficial in the prevention of osteoporosis. Oleuropein has an inhibitory effect against bone loss that occurs as a result of aging.…”
Section: Osteoporosismentioning
confidence: 99%
“…Reduction in the production of osteoblasts or increase in the incidence of osteoclasts is considered to be the main cause of osteoporosis. [ 57 ]…”
Section: Health Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33] On the contrary, elevated expression of TRPV1 is associated with atopic dermatitis in mice, and TRPV1 antagonists suppress dermatitis by inhibition of TRPV1 activation. 20,34 Basharat et al 35 showed that TRPV1 is essential for the reduction of ROS production and oxidative stress, pain sensation and inflammation, so TRPV1 has many health benefits. It was also suggested that, whenever TRPV1 is activated, it induces a second message through calcium influx in epidermal keratinocytes.…”
Section: Introductionmentioning
confidence: 99%